The factors that affect the formation and development of formal networks of micro and small enterprises Os fatores que afetam a formação e desenvolvimento de redes formais de micro e pequenas empresas - Consentino, Cristiano Gomes; Paiva, Ricardo Viana Carvalho de; Moura, Luiz Rodrigo Cunha (Revista Capital Científico - Eletrônica (RCCҽ) - ISSN 2177-4153, 2020)
The objective of this study is to analyze the factors and aspects - economic, management, marketing, among others - that influence in the association and in the development of the first formal network of micro and small enterprises (MSEs) in the retail industry of stationery stores from Brazil. The work had, as the unit of analysis, the first society of specific purpose (SSP) composed of 21 MSEs. Data were collected through a semi-structured interview script. The data interpretation was performed by means of a content analysis. The results classify the purchase SSP of MSEs as a new form of enterprise network with bureaucratic, symmetrical, owner, horizontal characteristics, long term, intangible, competitor inter-relation, with a structure free of barriers and sharing of solidary responsibility. The expectations divergence regarding the goals of individual firms influence the development of this SSP of MSE in the stationery stores sector in Brazil.